2016
DOI: 10.1039/c6ra21050c
|View full text |Cite
|
Sign up to set email alerts
|

An economic and environmentally benign approach for the preparation of monolithic silica aerogels

Abstract: One step sol–gel reaction, followed by solvent exchange free ambient pressure drying resulted in various monolithic silica aerogels from super-hydrophobic to hydrophilic with densities as low as 0.026 g cm−3 and thermal conductivities lower than air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…(d). The contact angle of silica xerogel was 60° that indicated hydrophilic surface of silica xerogel due to Si‐OH and ‐OH groups …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(d). The contact angle of silica xerogel was 60° that indicated hydrophilic surface of silica xerogel due to Si‐OH and ‐OH groups …”
Section: Resultsmentioning
confidence: 99%
“…The contact angle of silica xerogel was 60 ∘ that indicated hydrophilic surface of silica xerogel due to Si-OH and -OH groups. 51 Optimization studies for MB removal The values of RE and S/N ratio for each experiment are given in Table 2. Maximum value of average RE and S/N ratio were obtained wileyonlinelibrary.com/jctb Table 4.…”
Section: Characterization Of Silica Xerogelmentioning
confidence: 99%
“…The amphiphilic compound, Chol-OH, was synthesized according to our previous work. 41 Two immiscible phases were emulsified into stable Pickering emulsions using a homogenizer (IKA T10) at 11400 rpm for about 5 min. Moreover, the effects of the COP nanoparticle content (ranging from 0 to 0.05 g•mL −1 ), water content (ranging from 30 to 75%), PVA content (ranging from 0 to 3 wt %), and Chol-OH content (ranging from 0 to 0.04 g•mL −1 ) on the stability were systematically investigated, and the selected dosages in all tests are summarized in Table S1.…”
Section: Acs Appliedmentioning
confidence: 99%
“…The interfacial activity enables COP nanoparticles to adsorb and accumulate at the oil−water interface, forming a nanoparticle film, which is strengthened with the help of the amphiphilic molecule Chol-OH. 41 As a result, a series of Pickering emulsions containing COP nanoparticles were formed, and the stable starting emulsion droplets were used as templates for the successful preparation of COP monolithic foams. It has been demonstrated that the as-prepared COP monolith materials not only have good porosity and thermal stability but also exhibit compressibility and cuttability.…”
Section: Introductionmentioning
confidence: 99%
“…This property can be attributed to the three‐dimensional network structures that are built up through noncovalent interactions, such as hydrogen bonding, electrostatic interactions, van der Waals interactions and π – π interactions. Although several gelators are already used as hardeners for spilled fluids, cooking oils, cosmetic materials and paint thickeners, recent research on gelators has focused on their application to drug delivery and drug release in the field of biomaterials, scaffold materials for cells in tissue engineering, sensors, templates for the synthesis of inorganic nanostructures, auxiliary agents for producing organic electronics, electrolytes that prevent liquid leakage and detectors for explosives …”
Section: Introductionmentioning
confidence: 99%